Specialization of judicial and other authorities in the fight against environmental crime - Lukić, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The detection, investigation and prosecution of crimes against the environment has its specificity compared to other forms of crime, because of the nature of these crimes, the manner of execution (modus operandi) and the characteristics of their perpetrators. Although there is no objective need for modification of the rules of criminal procedure with regard to these offenses, there is an obvious need for a specialized body of the procedure (prosecutors, judges and authorized officers of the internal affairs). This is due the fact that only specific additional, specialized knowledge about the environmental issues, which is usually multidisciplinary, can provide high-quality, professional and competent research and detection of crimes against the environment. In this paper, the authors deal with the problems of specialization of judicial and other authorities in connection with criminal proceedings for offenses against the environment, of reasonableness and necessity, given the current situation in domestic practice, as well as some comparative solutions and experiences.